2019
DOI: 10.1111/jan.13915
|View full text |Cite
|
Sign up to set email alerts
|

Organizational determinants of bullying and work disengagement among hospital nurses

Abstract: Aims To identify organizational determinants of bullying and resulting work disengagement among hospital nurses. Design A cross‐sectional, web‐based, anonymous questionnaire study. Methods The questionnaire was administered in 2017 to all Registered Nurses in a regional healthcare system in the United States (N = 1,780), with 331 complete responses. Logistic regression was used to identify factors associated with personally experiencing and witnessing bullying, respectively. Linear regression was conducted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…First, WB can lower the self-esteem of employees. Both bullying that comes from superiors and colleagues can lead to the frustration of employees and lower self-esteem, and this type of "critical" aggression will undoubtedly reduce the PS of employees (Ouimet, 2013;Nguyen et al, 2017;Arnetz et al, 2019b). Therefore, after being bullied in the workplace, employees often choose to keep silent to prevent the harm caused by continuous resource loss.…”
Section: The Mediating Effect Of Psychological Safetymentioning
confidence: 99%
“…First, WB can lower the self-esteem of employees. Both bullying that comes from superiors and colleagues can lead to the frustration of employees and lower self-esteem, and this type of "critical" aggression will undoubtedly reduce the PS of employees (Ouimet, 2013;Nguyen et al, 2017;Arnetz et al, 2019b). Therefore, after being bullied in the workplace, employees often choose to keep silent to prevent the harm caused by continuous resource loss.…”
Section: The Mediating Effect Of Psychological Safetymentioning
confidence: 99%
“…Hoffman and Chunta (2015) highlighted the role of nurse managers in raising awareness with staff and the importance of addressing bullying immediately it is reported. Arnetz et al (2019) and Gilbert, Hudson, and Strider (2016) subsequently found that witnessing bullying greatly contributed to the willingness of the manager to implement steps to resolve the matter.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace violence is a frequently occurring problem that contributes to burnout . Current studies report that 35% to 60% of nurses experience bullying in the workplace .…”
Section: Contextmentioning
confidence: 99%
“…Workplace violence is a frequently occurring problem that contributes to burnout . Current studies report that 35% to 60% of nurses experience bullying in the workplace . One recent study reported up to 46% of nurses rating themselves in the “severe burnout” category, and another showed 60% of nurses experiencing psychosomatic symptoms of stress related to work .…”
Section: Contextmentioning
confidence: 99%